Complementary therapies for patients with systemic sclerosis. Issue 3 (October 2019) - Showalter, Kimberly; Hoffmann, Aileen; DeCredico, Nicole; Thakrar, Anjali; Arroyo, Esperanza; Goldberg, Isaac; Hinchcliff, Monique
Patients with systemic sclerosis often seek information regarding complementary and nutrition-based therapy. Some study results have shown that vitamins D and E, probiotics, turmeric, l-arginine, essential fatty acids, broccoli, biofeedback, and acupuncture may be beneficial in systemic sclerosis care. However, large randomized clinical trials have not been conducted. This review summarizes current data regarding various complementary therapies in systemic sclerosis and concludes with recommendations.